Students' gender, ICT attitude, computer self-efficacy and ICT engagement on use of ICT for learning mathematics among secondary mathematics students in Zanjan-Iran - Kaboodvand, Tahereh; Mohd Ayub, Ahmad Fauzi; Sulaiman, Tajularipin (Malaysia Association of Research and Education for Educators, 2018)
The purpose of this study is to determine ICT use in Mathematics learning based on gender, students' attitudes toward ICT, computer self-efficacy, and ICT engagement among secondary Mathematics students. In this study, 390 Mathematics students comprised of199 females and 191 males from 31 secondary schools in Zanjan-Iran were randomly selected by the sampling technique. A set of questioner was used to collect data for this study. Findings show that the combination of the three variables significantly predicted ICT use in Mathematics learning. Gender does not make any significant contribution to the prediction of the dependent variable. The study implies that a greater emphasis on the three independent variables narrows the gap in ICT use among students.